Iron status of young males and females performing weight-training exercise - DeRuisseau, K. C.; Roberts, L. M.; Kushnick, M. R.; Evans, A. M.; Austin, K.; Haymes, E. M. (Medicine & Science in Sports & Exercise, 2004)
PURPOSE: To determine the effect of weight training on measures of iron status in young males and females. METHODS: Forty (27 female, 13 male) non-weight-trained college age subjects participated in a 12-wk weight-training program conducted 3 d.wk-1. Blood samples and food diaries were obtained pretraining and at 4-wk intervals. Blood was analyzed for hemoglobin, hematocrit, serum iron (SI), total iron binding capacity (TIBC), transferrin saturation (TS), serum ferritin (SF), soluble transferrin receptor (sTfR), and creatine kinase (CK). Subjects were grouped by SF level (FL, females < or = 20 microg.L-1; FN, females > 20 microg.L-1; ML, males < or = 45 microg.L-1; MN, males > or = 50 microg.L-1) to determine the impact of initial iron status on measured responses. RESULTS: Weight training increased strength and fat-free mass and decreased levels of percent body fat. Hemoglobin concentration declined after 12 wk of training (13.7 +/- 1.6 vs 13.2 +/- 1.7 g.dL-1), independent of gender or initial iron status. Only the MN group experienced a decline in SF level after 8 wk of training (129.7 +/- 77.9 vs 102.0 +/- 57.8 microg.L-1). No significant changes were observed for hematocrit, SI, TIBC, TS, sTfR, or CK measures. Total iron intake, but not heme or bioavailable iron intakes, declined at the 12th week of training compared with baseline (13.4 +/- 6.5 vs 10.7 +/- 4.8 mg.d-1) and was not significantly correlated with hematological or iron status measures. CONCLUSIONS: Hemoglobin concentration declines without alterations in SI, TIBC, TS, or sTfR after 12 wk of weight training. The SF level of males with adequate iron status is lowered with weight training but not among females or males with low iron status.